Synthesis and characterization of cationic-diutan gum to enhance thermal stability for oil & gas application - Norhanis, Arbaa'in (2024)
Water-based fluids have been used for centuries in oil and gas applications. Technological advancements, particularly the addition of clay, polymer material, and many other substances into the water-based fluids, were made to create a robust fluid system to suit the demands of various reservoir conditions and to enhance oil and gas production. The fluids can be tailored for water-soluble polymers with viscosifying or gelling properties. As the oil and gas in the shallow wells become depleted, the oil and gas exploration has moved into deeper and more extreme reservoir conditions, which limited the performance of the currently available gelling fluids. At high temperatures, the gelling fluids will experience degradation and lose their viscosity. To preserve environmental safety, it is more favorable to improve 'green' gelling fluid produced from biopolymer material instead of changing focus towards synthetic polymers with only slightly better thermal stability. Amongst the biopolymers, diutan gum (DG) was chosen due to its high molecular weight and double helical structure. The application of DG can still be considered new in the oil and gas industry; therefore, many of its potentials need to be explored. The cationization of DG was conducted in this research to further enhance the properties of DG. Cationic diutan gum (CDG) biopolymer was developed to improve the thermal and rheological properties of water-based gelling systems for upstream petroleum applications. The modification process involved incorporating a quaternary amine group onto the diutan gum (DG) structure by mixing DG with varying concentrations of N-(3-chloro-2-hydroxypropyl) trimethyl ammonium chloride (CHPTAC) in the presence of sodium hydroxide as a catalyst. The cationization resulted in a decrease in %H from 5.54% to 3.81% and an increase in %N from 0.72 to 0.83, indicating the successful formation and grafting of CHPTAC onto the polysaccharide structure. Fourier transform infrared spectroscopy (FTIR) confirmed the incorporation of cationic moieties into the CDG chains, observed through an increase in the intensity of the C–N stretching vibration peak at 1411 cm-1 . Field emission scanning electron microscopy (FESEM) revealed that the smooth surface of DG transformed into a connective spherical reticular structure upon CHPTAC modification. The viscosity of the CDG gelling fluid increased due to electrostatic chain interaction, except for CDG with higher CHPTAC concentrations, which exhibited decreased viscosity. Additionally, the viscoelasticity properties displayed a plateau-like region, indicating a stable gel response towards frequency and excellent suspension capability of CDG. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) demonstrated a slight improvement in thermal characteristics for CDG compared to DG. Furthermore, the thermal stability analysis using a static thermal aging test confirmed that CDG remained stable up to 170 °C, highlighting its potential to meet the high-temperature requirements of the upstream petroleum industry. In conclusion, the development of cationic diutan gum (CDG) presents a promising approach for enhancing the thermal and rheological properties of water-based gelling systems, making it a potential candidate for various challenging oil and gas reservoir conditions